Using Radical Adult Education to Map Change in a Globalized World - Michelle Glowacki-Dudka; Amy Ward; Stephen Whikehart; Cathy Mullett; Jennifer Warrner; Heidi Burkett; Antonette Payne; Mary E. Borst (Adult Education Research Conference, 2016)
Radical adult education using a sociological frame can support adult educators to see their roles as change agents within their spheres of influence. Using cultural mapping, adult educators define these spheres, stake claims, set benchmarks, grow networks, or develop participatory action research within the identified community.
Keywords: Radical adult education; cultural mapping; transformative learning